Role of Swallowing Therapy in Preventing Aspiration Pneumonia in Patients with Stroke having Dysphagia - Nauman, Bisma; Tassadaq, Naureen (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the effectivity of swallowing therapy in prevention of aspiration pneumonia in patients with acute stroke with dysphagia admitted to the Intensive Care Unit. Study Design: Prospective comparative study. Place and Duration of Study: Department of Rehabilitation Medicine, Fauji Foundation Hospital, Rawalpindi Pakistan, from Jun-Dec 2023 Methodology: A total of 120 patients were recruited, patients were randomly divided into two groups. Group-S (n=60) receivied swallowing therapy and Group-N (n=60) received standard nursing care for oral feed according to institutional protocol. Primary variables studied were median scores of the Functional Oral Intake Scale (FOIS) (Scored 1-7) and Swallow Function Score System (SFSS) (Scored 0-6) evaluated every day and complied after 10 days along with incidence of aspiration pneumonia and necessity to shift to NG feed in case of complete oral feed failure. Results: Median functional oral intake scale was 4.00 (0.00) in Group-N versus 6.00 (0.00) in Group-S (p<0.001). Median swallow function score system was 4.00 (1.00) in Group-N versus 5.00 (0.00) in Group-S (p<0.001). The incidence of aspiration pneumonia was seen in 20(33.3%) patients in Group-N versus 05(8.3%) patients in Group-S (p=0.001). Patients shifted to nasogastric feed following oral intake failure were 20(33.3%) patients in Group-N versus 02(3.3%) patients in Group-S. Conclusion: The swallowing therapy results in early and effective initiation of oral feed with decreased need for nasogastric feeding resulting in reduced duration of hospital stay in selected patients having stroke with dysphagia.